Stimulating The Reading Proficiency Of 10th Grade Students Through The Application Of Wordwall In Recount Text - Cahya Rika Prapelia; Dian Fadhilawati (Jurnal Riset Rumpun Ilmu Bahasa, 2024)
The study aims to evaluate the efficacy of the Wordwall application in stimulating reading skills among tenth-grade students at X-10 in SMA 1 Sutojayan. It employs a pre-experimental design with a one-group pre-test and post-test methodology, following a quantitative research framework. The process includes three stages: 1) pre-test, 2) treatment, and 3) post-test. To ensure data reliability, tests were piloted on students with similar proficiency levels. Data collection involved administering tests, and statistical analysis. Results showed a significant improvement in student reading achievement, with scores increasing from 77.24 to 86.24 after implementing the Wordwall application for recount text instruction. The paired sample t-test showed the distinction (p = 0.000), underscoring the Wordwall application's effectiveness in enhancing recount text reading achievement among tenth-grade students at X-10 in SMA Negeri 1 Sutojayan Blitar.